Can performance-based budgeting reform improve corporate environment in ESG? Evidence from Chinese-listed firms - Wang, Xueping; Hu, Shichao (Frontiers in Environmental Science, 2022)
Finance has been confirmed as a pillar industry of the national governance. It provides a solid guarantee for achieving the Double Carbon target official. How to give full play to the role environmental governance in the reform of the fiscal and taxation systems and motivate enterprises to enhance their environment in Environmental, Social and Governance (EESG) is worth investigating in depth. In this study, A-share listed companies in China from 2001 to 2020 are taken as the examples. The effect of the performance-based budgeting (PBB) reform on the enterprise EESG is empirically examined through quasi-natural experiments using a multi-time difference-in-difference model. We find that PBB has significantly optimized the enterprise EESG. The placebo test, the difference-in-difference-in-difference method, and a series of other robustness tests all support the above conclusion. Furthermore, it is suggested that the environmental governance effect of PBB is more significant in the areas with heavy financial pressure and stronger government audit. For enterprises with government contracts, strong green innovation capabilities or high financing constraints, the environmental governance effect of the PBB reform is more significant. The mechanism test is performed, and the result suggests that the influence mechanism of this environmental governance role lies in the fact that PBB has improved environmental protection subsidies and enhanced fiscal transparency. Through the economic consequences test, we find that enterprise EESG can bring economic benefits to enterprises, which is reflected in the improvement of enterprise return on total assets, price-to-book ratio, and total patent authorization. This study enriches the literature of the economic consequences of PBB, and it takes on a certain reference significance in deepening the current fiscal and tax system reform and vigorously optimizing the major strategy of carbon peak and carbon neutrality.